La práctica del voleibol y el desarrollo de las capacidades condicionales y coordinativas en los alumnos de octavo, noveno y décimo año de educación básica de los colegios Emiliano Abendaño González y Monseñor Leónidas Proaño del cantón Catamayo, periodo lectivo 2012 – 2013, propuesta práctica metodológica - González Cano, Claudio Emanuel (2014)
To carry out the present research work is first fixed a direct observation of the events that arise in schools both during daily activities undertaken by the students, then the topic of this thesis is formulated: VOLLEYBALL PRACTICE AND DEVELOPMENT OF CONDITIONAL and coordinative abilities STUDENTS IN EIGHTH, NINTH AND TENTH YEAR BASIC EDUCATION SCHOOLS BISHOP EMILIANO ABENDAÑO GONZÁLEZ AND LEONIDAS PROAÑO CATAMAYO CANTON, LECTIVO PERIOD 2012 -. 2013 And the underlying problem relates How does playing volleyball in the development of conditional and coordinative skills in the eighth, ninth and tenth year of Basic Education Schools Abendaño Emiliano González and Bishop Leonidas Proaño Catamayo Canton, academic year 2012 - 2013? The overall objective is to verify whether the incipient development of conditional and coordinative abilities is impacting athletic training students in eighth, ninth and tenth year of basic education schools Abendaño Emiliano González and Bishop Leonidas Proaño Canton Catamayo period 2012 -2013. We used a methodology consistent with the research and the following methods were applied: scientific, deductive method, synthetic analytical method, descriptive method, statistical method. Among the most important in both the conclusions and the recommendations results we need by implementing surveys and test students have been able to verify that the incipient development of the Probation and capabilities coordinative impact on sports training of students in eighth, ninth and Tenth year of basic education school Emiliano Abendaño and Bishop Leonidas Proaño finally recommended that teachers of Physical Culture, implement teaching strategies for stimulating physical sport students and have a positive effect on their overall development and therefore requires prior planning, where the required strategies, according to the needs required by the student designed.